ATTENUATION OF SODIUM FLUORIDE INDUCED NEPHROTOXICITY BY FRESH ORANGE JUICE IN MICE - S. Andleeb; Ata-ul-Mustafa Fahid; U. F. Dilawari; M. Arshad; C. Ara (Journal of Animal and Plant Sciences, 2018)
Fluoride is natural contaminant of underground water and targets the living organisms through drinking water. Fruits are well known for being rich in antioxidants to combat toxins. This study was aimed to explore the ameliorative strength of freshly squeezed orange juice against the reno-toxicity induced by sodium fluoride in mice. For this purpose, 4 weeks old male albino mice were divided randomly into five groups of 5 mice each. Group C was intact, untreated control given 0.00µg/g BW of sodium fluoride, while DI and DII were the groups of animals treated with 0.1 ml of 5.0 and 7.5µg/g BW of sodium fluoride administered for 30 days respectively. Groups D III and D IV were treated with 0.1 ml of 5.0 and 7.5µg/g BW of sodium fluoride administered orally for first 30 days and then 0.1 ml of freshly squeezed orange juice (50% in distilled water) for next 30 days respectively. Whole study was conducted under controlled environmental conditions of temperature 25±1°C and humidity 40-50%. At the end of experiment, mice of each group were weighed, anaesthetized and processed for recovery of kidneys with subsequent fixation using Bouinsfixative. Morphometric analysis showed an overall significant (p<0.05) reduction in body weight of mice of group DI(23.2g) and DII( 20.8g) as compared to group C(29g) . While bodyweight of group DIII(27.40g) and DIV ( 26.80g)treated with orange juice as antidote was in close adherence to those of group C. Almost similar trend was observed for kidney length and diameter. Kidney length of group DI (9.088mm), DII (8.528mm) and DIV (8.826mm) was reduced significantly as compared to group C (9.948mm). Non-significant difference for kidney length in group DIII (9.774mm) as compared to control is indicative of ameliorative potential of orange juice. Diameter of kidney was also found significantly different for group DI ( 5.188mm), DII(4.886mm) , and DIV (5.182mm) as compared to group C (5.728mm). Group DIII (5 .620mm) again was insignificantly different for kidney diameter against group C. In micrometric study, the mean cross sectional area of 2 2 glomeruli was found reduced significantly in group DI(2043µ ) and DII(14287.6µ ) as compared to control group C 2 2 2 (37565.55µ ) while a significant increase was observed for group DIII(21846.1 µ ) and DIV(21731.9 µ ) as compared to groups DI and DII. In histopathological analysis, glomerular shrinkage was observed in groups DI and DII. Fresh orange juice has been found to improve this deterioration in group DIII and DIV. These results suggest that sodium fluoride is reno- toxic at different sub lethal doses and orange juice having a variety of natural anti-oxidants, is a potential candidate to attenuate these toxicities. (Song et al., 2017) ; neuropathological alterations ( Balaji
Keywords: Sodium fluoride; Reno toxicity; Mice; Shrunken Glomeruli; Musmusculus.